Using Body Gesture in Demonstrating and Understanding English Proverbs - Joko Prayudha.S (English Language and Education Spectrum, 2023)
Understanding proverbs in English is one of the materials that must be studied in English literature lessons at school. Proverbs are one of the oldest types of literature that have ever existed, and they are a type of literary work that must be mastered because proverbs themselves have meanings, goals, and values that are very beneficial to students. Through understanding literary material, students can learn valuable lessons in interpreting the meaning of the sentences conveyed. Therefore, this research aims to find out students' opinions on using body gestures to demonstrate and understand the meaning of proverbs in English. The method used in this research is qualitative research through a descriptive approach. The informants in this study were 36 students who took selective English literature subjects. Data were obtained through direct observation of learning activities and interviews to obtain more comprehensive information. After the data is collected, it is analyzed through three stages: data reduction, data display, and data conclusion. The results of the study show that utilizing body gestures in learning proverbs can help people more easily understand the meaning and significance of a proverb. In addition, students are also encouraged to be more active and motivated to be involved in learning activities because the learning situation becomes more enjoyable.